Theoretical and computational study of a notch in soft solid - Chu, Wee Sheng (2019)
The motivation of this study is to investigate the stress singularity of a notch in soft solid under finite out of plane compression by greater level of elasticity. Stress singularity is essential as future uses of soft bodies include soft robotics and even replacement for human organs. First, we study the equations from the strain energy density. This will give the strain invariants which will enable us obtain the first Piola-Kirchhoff stresses. Then, a software known as Mathematica will assist us in obtaining the stress singularity in relation to the notch. While studying the notches, we will also vary the notches angle to determine and compare the stress exponent values. These results are vital and able to help us to design a material of lower stress exponent.